Weekly Training Frequency Effects on Strength Gain: A Meta-Analysis - Grant W. Ralston; Lon Kilgore; Frank B. Wyatt; Duncan Buchan; Julien S. Baker (SpringerOpen, 2018)
Abstract Background The current recommendations for resistance training (RT) frequency range from 2 to 5 days per week (days week− 1) depending on the subjects' training status. However, the relationship between RT frequency and muscular strength remains controversial with reported variances existing across different population groups. We conducted a meta-analysis that (1) quantified the effects of low (LF; 1 day week− 1), medium (MF; 2 days week− 1), or high (HF; ≥ 3 days week− 1) RT frequency on muscular strength per exercise; (2) examined the effects of different RT frequency on one repetition maximum (1RM) strength gain profiles (multi-joint exercises and single joint exercises); (3) examined the effects of different RT frequency on 1RM strength gain when RT volume is equated; and (4) examined the effects of different RT frequency on 1RM strength gains on upper and lower body. Methods Computerised searches were performed using the terms 'strength training frequency', 'resistance training frequency', 'training frequency', and 'weekly training frequency'. After review, 12 studies were deemed suitable according to pre-set eligibility criteria. Primary data were pooled using a random-effects model. Outcomes analysed for main effects were pre- to post strength change with volume-equated studies that combined multi-joint and isolation exercise; isolation-only exercise and untrained subjects only. Heterogeneity between studies was assessed using I 2 and Cochran's Q statistics with funnel plots used to assess publication bias and sensitivity analyses calculated for subgroups. Results Pre- versus post-training strength analysis comprised of 74 treatment groups from 12 studies. For combined multi-joint and isolation exercises, there was a trend towards higher RT frequency compared with lower frequency [mean effect size (ES) 0.09 (95% CI − 0.06-0.24)] however not significant (p = 0.25). Volume-equated pre- to post-intervention strength gain was similar when LF was compared to HF [mean ES 0.03 (95% CI − 0.20-0.27); p = 0.78]. Upper body pre- to post-intervention strength gain was greater when HF was compared with LF [mean ES 0.48 (95% CI 0.20-0.76)] with significant differences between frequencies (p < 0.01). Upper body pre- to post-intervention strength gain was similar when MF was compared with LF (ES 0.12; 95% CI − 0.22-0.47); p = 0.48]. There was no significant difference in lower body mean ES between HF and LF [mean ES 0.21(95% CI − 0.55-0.13); p = 0.22]. There was a trend towards a difference in mean ES between MF and HF [mean ES 0.41(95% CI − 0.26-1.09); however, the effect was not significant (p = 0.23). Conclusions The existing data does not provide a strong correlation between increased weekly training frequency (HF) and maximal strength gain in upper and lower body resistance exercises for a mixed population group. When RT is volume-equated for combined multi-joint and isolation exercises, there is no significant effect of RT frequency on muscular strength gain. More investigations are required to explore the effects of varying weekly training frequencies adequately.